Novel FGF9 variant contributes to multiple synostoses syndrome 3. Issue 7 (22nd March 2022) - Dobson, Stephanie M.; Kiss, Courtney; Borschneck, Daniel; Heath, Karen E.; Gross, Adrian; Glucksman, Marc J.; Guerin, Andrea
Abstract: Multiple synostoses syndromes (SYNS) are autosomal dominant syndromes characterized by multiple joint fusions commonly involving the carpal‐tarsal, interphalangeal, humeroradial, and cervical spine joints. They display genetic heterogeneity with pathogenic variants reported in four separate genes ( NOG, GDF5, FGF9, and GDF6 ) defining four different SYNS forms. FGF9 variants have been reported in SYNS3, a SYNS with multiple synostoses, normal cognition, normal hearing, and craniosynostosis. Here, we report a novel FGF9 c.569G > C p.(Arg190Thr) variant identified by whole‐exome sequencing in a patient with multiple bony abnormalities. The patient initially presented with elbow instability and decreased range of motion. Imaging revealed bilateral radial head deformities, carpal‐tarsal fusions, brachydactyly, and osteoarthritis of the sacroiliac joints. In silico protein modeling of the identified FGF9 variant predicts decreased stability of ligand‐receptor binding supporting the pathogenicity of this finding. This finding expands the repertoire of FGF9 variants and phenotypic information reported for SYNS3 and suggest that genotype phenotype correlations due to localization seem less likely and more so due to the consequence of the pathogenic variant on the receptor. This is useful in the counseling in families as more de novo variants emerge.